Electronic structure and magnetic properties of FeWO 4 nanocrystals synthesized by the microwave-hydrothermal method - Almeida, M. A. P.; Cavalcante, L. S.; Morilla-Santos, C.; Lisboa Filho, Paulo Noronha [UNESP]; Beltrán, A.; Andrés, J.; Gracia, L.; Longo, Elson [UNESP] (Elsevier, 2012)
This communication reports that FeWO 4 nanocrystals were successfully synthesized by the microwave-hydrothermal method at 443 K for 1 h. The structure and shape of these nanocrystals were characterized by X-ray diffraction, Rietveld refinement, and transmission electron microscopy. The experimental results and first principles calculations were combined to explain the electronic structure and magnetic properties. Experimental data were obtained by magnetization measurements for different applied magnetic fields. Theoretical calculations revealed that magnetic properties of FeWO 4 nanocrystals can be assigned to two magnetic orderings with parallel or antiparallel spins in adjacent chains. These factors are crucial to understanding of competition between ferro- and antiferromagnetic behavior. © 2012 Elsevier Inc.
Keywords: Clusters; Crystal growth; Electronic properties; Magnetic measurements; Adjacent chains; Antiferromagnetic behaviors; Applied magnetic fields; First-principles calculation; Magnetization measurements; Microwave-hydrothermal methods; Theoretical calculations; Antiferromagnetism; Electronic structure; Magnetic properties; Magnetic variables measurement; Rietveld refinement; Transmission electron microscopy; X ray diffraction; Nanocrystals